2008
DOI: 10.1097/tp.0b013e31817ba9e3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease and Hypertension Risk in Living Kidney Donors: An Analysis of Health Administrative Data in Ontario, Canada

Abstract: Based on administrative data, the risk of cardiovascular disease was unchanged in the first decade after kidney donation. The observed increase in diagnosed hypertension may be due to nephrectomy or more blood pressure measurements received by donors in follow-up and requires prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 34 publications
0
115
1
Order By: Relevance
“…Among living donors with private health insurance, African Americans and Hispanics have an increased risk of hypertension and diabetes and an incidence of ESRD of 0.13% at a median 7.7 years of follow-up after donation (6). The rate of selected comorbid conditions, including cancers, cardiovascular disease, depression, and fractures, following living donation is also generally similar to that among individuals characterized as the "healthiest" portion of the general population and among age-and sex-matched controls with commercial insurance (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 62%
“…Among living donors with private health insurance, African Americans and Hispanics have an increased risk of hypertension and diabetes and an incidence of ESRD of 0.13% at a median 7.7 years of follow-up after donation (6). The rate of selected comorbid conditions, including cancers, cardiovascular disease, depression, and fractures, following living donation is also generally similar to that among individuals characterized as the "healthiest" portion of the general population and among age-and sex-matched controls with commercial insurance (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 62%
“…In the absence of a non-donor control population, the extent to which incident hypertension is attributable to kidney donation is difficult to judge. A retrospective study of over 1,200 living kidney donors, with a mean follow-up of 6.4 years, found that donors had a 40% increased risk (hazard ratio, 1.4; CI, 1.2-1.7) of being diagnosed with hypertension compared with that of non-donor controls (24). A recent study from the UK pooled 8 Lisinopril 9 ---10 ---11 ---12 ---13 ---14 ---15 ---16 ---17 ---18 ---19 --Atenolol 20 --HCTZ 21 ---HCTZ, hydrochlorothiazide.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also noted that donors were seen more often by their primary care physicians, raising the possibility that the increased prevalence might have been due to increased monitoring. 44 In the University of Minnesota Study, mean 'office' systolic BP in the 255 patients following nephrectomy was 122 mm Hg, significantly lower than an age-matched control population. 35 The prevalence of hypertension requiring drug therapy was 25%, not significantly different from the figure of 29% in the control population.…”
Section: Risk Of Hypertension After Kidney Donationmentioning
confidence: 99%